Peran Non-Governmental Intermediary dalam Menjembatani Petani dan Pemerintah: Model Kelembagaan Baru untuk Akselerasi Reforma Agraria - Muhamad Febri Pribadi; Regina Agneshia Hannaningdyah; Muhammad Anas Ulil Abshor Munif; Nataneila Astya Putri Asmana; Aprila Niravita; Muhammad Adymas Hikal Fikri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research analyzes the strategic role of the Non-Governmental Intermediary (NGI) in bridging farmers and the government to accelerate the implementation of Agrarian Reform (RA) in Indonesia. Sharp agrarian inequality, driven by colonial legacy, land control by corporations/elites, and slow RA due to bureaucratic complexity, overlapping authorities, and information gaps, creates an urgent need for new collaboration mechanisms. NGIs fill this void by performing a multidimensional role: Dialogue Facilitator to reduce information asymmetry; Technical Assistant through Participatory Mapping and valid administrative document preparation; Community-Based Agrarian Conflict Mediator; Independent Monitor for accountability; and Policy Advocate. A New Institutional Model based on Hybrid Governance is proposed, formally integrating the state, NGIs, and farming communities, supported by Technological Integration for transparent participatory spatial data. This model must be realized through Institutionalized Partnership (MoU/Presidential Regulation) to ensure legitimacy and sustainability. Key challenges include bureaucratic resistance, NGO stigma, and local elite conflicts of interest, but strengthening the NGI role presents opportunities through enhanced public accountability and technical innovation. In conclusion, the successful acceleration of RA hinges on the formal legal recognition and capacity building of NGIs as official actors within the RA institutional framework.